2021
DOI: 10.3389/fonc.2021.749083
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Response Biomarkers of Apatinib in the Treatment of Malignancies in China: A Review

Abstract: Apatinib is a multitarget tyrosine kinase inhibitor marketed in China for the treatment of advanced gastric cancer (GC) and hepatocellular carcinoma (HCC). It has also been used off-label for the treatment of many other malignancies. To comprehensively evaluate the efficacy of apatinib as a targeted therapy in the treatment of malignancies, we conducted systematic online and manual searches of the literature on apatinib in the treatment of malignancies. In this review, we first summarized the efficacy of apati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 85 publications
1
18
0
Order By: Relevance
“…Although several studies have proposed that PD-1 inhibitors or apatinib have a beneficial effect on the survival outcome of advanced CRC patients, the prognosis of advanced CRC is still far from satisfactory ( 8 , 10 , 29 ). Given that satisfactory survival rates have been achieved by PD-1 inhibitors plus apatinib in patients with advanced cancer ( 30 , 31 ), it could be assumed that patients with advanced CRC may have better survival outcomes after treatment with PD-1 inhibitors plus apatinib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies have proposed that PD-1 inhibitors or apatinib have a beneficial effect on the survival outcome of advanced CRC patients, the prognosis of advanced CRC is still far from satisfactory ( 8 , 10 , 29 ). Given that satisfactory survival rates have been achieved by PD-1 inhibitors plus apatinib in patients with advanced cancer ( 30 , 31 ), it could be assumed that patients with advanced CRC may have better survival outcomes after treatment with PD-1 inhibitors plus apatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib is an innovative Chinese vascular epithelial growth factor receptor-2 inhibitor that suppresses tumor angiogenesis ( 8 , 9 ). It has been reported that apatinib shows satisfactory efficacy in various advanced cancers, including CRC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apatinib was initially approved for use in China for patients with previously treated advanced adenocarcinoma of stomach or gastroesophageal junction ( 34 ). Later, the usage of apatinib was extended to various cancers, mainly gastric cancer, esophageal cancer, hepatocellular carcinoma, BC, lung cancer, sarcoma, and colorectal cancer ( 35 ). Apatinib monotherapy is usually administered at the end of the treatment period or in cases of intolerance to other treatments in patients with ABC.…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib was approved for increased use in China for the treatment of patients with advanced HCC who had previously failed or were intolerant to at least one first-line systemic therapy in December 2020. TACE in combination with Apatinib was superior to TACE alone in the long-term treatment of advanced HCC ( 12 , 13 ), while apatinib could be used as second-line treatment in advanced HCC therapy. However, the most suitable agent combined with apatinib in TACE treatment needs to be identified.…”
Section: Introductionmentioning
confidence: 99%